Molecular mechanisms of extracellular-ATP-mediated colorectal cancer progression: Implication of purinergic receptors-mediated nucleocytoplasmic shuttling of HuR - Abdel-Aziz S. Shatat; Elsayed M. Mahgoup; Mohammed H. Rashed; Ibrahim G. Saleh; El-Sayed Akool (Purinergic Signalling, 2024)
One of the leading causes of cancer-related deaths worldwide is colorectal cancer (CRC). Extracellular ATP (e-ATP) and purinergic receptors (P2R) play a central role in CRC proliferation and progression. Human antigen R (HuR) is becoming more and more understood to be essential for the expression of genes linked to cancer. The current study demonstrates that ATP can mediate CRC (Caco-2 cells) progression via induction of HuR nucleocytoplasmic shuttling and subsequent expression of cancer-related genes, a consequence mostly mediated via the P2R receptor. It was also noted that suppression of HuR activity by using dihydrotanshinone I (DHTS) prevents cancer-related gene expression and subsequent CRC (Caco-2 cells) progression induced by ATP. The expression of cyclin A2/cyclin-dependent kinase 2 (CDK2), Bcl-2, ProT-α, hypoxia‐inducible factor1-α (HIF1-α), vascular endothelial growth factor A (VEGF-A), transforming growth factor-β (TGF-β) and matrix metallopeptidase 9 (MMP-9) induced by ATP were highly reduced in the presence of either PPADS (non-selective P2R antagonist) or DHTS. In addition, e-ATP-induced Caco-2 cell proliferation as well as cell survival were highly reduced in the presence of either PPADS or DHTS or selective CDK-2 inhibitor (Roscovitine) or selective Bcl-2 inhibitor (ABT-263). Furthermore, it was found that MMP-9 is critical for Caco-2 cells migration induced by e-ATP as demonstrated by a clear reduction in cells migration in the presence of a selective MMP-9 inhibitor (Marimastat). Collectively, these data demonstrate that ATP through P2R activation can induce HuR nucleocytoplasmic shuttling that could be translated into an increase in cancer-related genes expression and subsequent, cell proliferation and progression.

Sorafenib and edaravone protect against renal fibrosis induced by unilateral ureteral obstruction via inhibition of oxidative stress, inflammation, and RIPK-3/MLKL pathway - Mohamed A. Abou Taha; Fares E.M. Ali; Ibrahim G. Saleh; El-Sayed Akool (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Renal fibrosis is the common endpoint of nearly all chronic and progressive nephropathies. Cell death and sterile inflammation are the main characteristics of renal fibrosis, which can lead to end-stage renal failure. The inflammatory reaction triggered by tissue damage is strongly related to necroptosis, a type of caspase-independent, regulated cell death. Using an animal model of unilateral ureteral obstruction (UUO), the anti-fibrotic effects of sorafenib (SOF), a multi-kinase inhibitor, and edaravone (EDV), a potent antioxidant and free radical scavenger, were examined in rats with obstructive nephropathy. Experimentally, animals were divided randomly into five groups: sham; UUO; UUO + SOF (5 mg/kg/day, P.O.); UUO + EDV (20 mg/kg/day, P.O.); and UUO + SOF + EDV groups. The kidney function biomarkers, oxidant/antioxidant status, renal mRNA expressions of TNF-α, collagen-1α, protein expressions of RIPK-1, RIPK-3, MLKL, caspase-8, HYP, MPO, and TNF-α were all significantly modulated by UUO. Administration of either SOF or EDV significantly attenuated cellular and molecular changes induced by UUO. Also, histopathological changes were improved. Moreover, SOF in combination with EDV, significantly improved UUO-induced renal fibrosis compared with each drug alone. Collectively, administration of either SOF or EDV or both of them significantly attenuated the rats with obstructive nephropathy, possibly by blocking the RIPK-3/MLKL necroptotic pathway and suppressing renal oxidative stress and inflammation.

P2 X 7 receptor is a critical regulator of extracellular ATP-induced profibrotic genes expression in rat kidney: implication of transforming growth factor-β/Smad signaling pathway - Fatma Mounieb; Somaia A Abdel-Sattar; Amany Balah; El-Sayed Akool (Purinergic Signalling, 2024)
This study was designed to investigate the potential of extracellular adenosine 5′-triphosphate (ATP) via the P2 X 7 receptor to activate the renal fibrotic processes in rats. The present study demonstrates that administration of ATP rapidly activated transforming growth factor-β (TGF-β) to induce phosphorylation of Smad-2/3. Renal connective tissue growth factor (CTGF) and tissue inhibitor of metalloproteinase-1 (TIMP-1) mRNA and protein expressions were also increased following ATP administration. A decrease in TGF-β amount in serum as well as renal Smad-2/3 phosphorylation was noticed in animals pre-treated with the specific antagonist of P2 X 7 receptor, A 438,079. In addition, a significant reduction in mRNA and protein expression of CTGF and TIMP-1were also observed in the kidneys of those animals. Collectively, the current findings demonstrate that ATP has the ability to augment TGF-β-mediated Smad-2/3 phosphorylation and enhance the expression of the pro-fibrotic genes, CTGF and TIMP-1, an effect that is largely mediated via P2 X 7 receptor.

Cyclosporin A activates human hepatocellular carcinoma (HepG2 cells) proliferation: implication of EGFR-mediated ERK1/2 signaling pathway - Mohammed E. Abo-El Fetoh; Gouda K. Helal; I. G. Saleh; M. Ewees; Mohamed ElShafey; Mohamed R. Elnagar; El-Sayed Akool (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Propolis alleviates concanavalin A-induced hepatitis by modulating cytokine secretion and inhibition of reactive oxygen species - Fatma Mounieb; Laila Ramadan; El-Sayed Akool; Amany Balah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

All-trans retinoic acid potentiates cisplatin-induced kidney injury in rats: impact of retinoic acid signaling pathway - Abdelrahman M. Elsayed; Tamer M. Abdelghany; El-Sayed Akool; Abdel-Aziz H. Abdel-Aziz; Mohamed S. Abdel-Bakky (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)